INSECTICIDAL EFFECT OF THE ALPHA-SHAKTI PREPARATION AGAINST FLIES AND PATHORS - Elmurodov B. A., Professor; Pulotov F. S., v.f.f.d.; Axmedov B. N., v.f.n.; Murodov X. U., v.f.f.d. (Web of Journals Publishing, 2024)
This article provides data on the insecticidal properties of the drug alpha-shakti against down feather eaters, one of the most common ectoparasites of poultry farming in recent years.
Keywords: alpha-shakti, poultry, pheasant, pheasant, insecticide, concentration, parasite, pyrethroid, ectoparasite, emulsion.